Efficacy of sulfasalazine in patients with inflammatory back pain due to undifferentiated spondyloarthritis and early ankylosing spondylitis: a multicentre randomised controlled trial. Issue 9 (10th April 2006) - Braun, J; Zochling, J; Baraliakos, X; Alten, R; Burmester, G; Grasedyck, K; Brandt, J; Haibel, H; Hammer, M; Krause, A; Mielke, F; Tony, H-P; et al.
Abstract : Objectives: To assess the effect of sulfasalazine (SSZ) on inflammatory back pain (IBP) due to active undifferentiated spondyloarthritis (uSpA) or ankylosing spondylitis in patients with symptom duration <5 years. Methods: Patients with IBP and a Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) >3 from 12 centres were randomly assigned to 24 weeks' treatment with SSZ 2 g/day or placebo. The primary outcome variable was the change in BASDAI over 6 months. Secondary outcomes included measures of spinal pain, physical function and inflammation. Results: 230 patients (50% men, age range 18–64 years, 67% human leucocyte antigen B27 positive) were treated with either SSZ 2×1 g/day or placebo for 6 months. Enthesitis was found in 50%, and peripheral arthritis in 47% of the patients. The mean (SD) BASDAI dropped markedly in both groups: by 3.7 (2.7) and 3.8 (2.4), respectively, as did most secondary outcome measures. No noticeable difference in treatment was observed between groups. Patients with IBP and no peripheral arthritis had significantly (p = 0.03) more benefit with SSZ (BASDAI 5.1 (1.3) to 2.8 (2.3)) than with placebo (5.2 (1.6) to 3.8 (2.4)). Spinal pain (p = 0.03) and morning stiffness (p = 0.05) improved with SSZ in these patients, but other secondary outcomes were not markedly different. Conclusion: SSZ was no better than placebo for the treatment of the signs and symptoms of uSpA; however, SSZ was more effective than placebo in the subgroup of patients with IBP and no peripheral arthritis.